2017
DOI: 10.1021/acs.est.7b04106
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphate Triesters and Diester Degradation Products in Municipal Sludge from Wastewater Treatment Plants in China: Spatial Patterns and Ecological Implications

Abstract: Little is known about the occurrences, distributions, sources, and potential risks of organophosphate (OP) triesters and diester degradation products in municipal sludge from wastewater treatment plants (WWTPs). In this study, we conducted the first nationwide survey to simultaneously determine a suite of 11 OP triesters and six diester degradation products in sludge from WWTPs across China. All OP triesters were detected and three diesters were identified for the first time in sludge samples. Total concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 53 publications
(195 reference statements)
5
102
3
Order By: Relevance
“…The transformation of OP flame retardants in indoor and outdoor environments has been reported but has been poorly characterized . Fu et al reported the estimated half‐lives for Cl‐PFRs to be higher than those for non‐chlorinated ones using EPI Suite version 4.11 . Since the uptake of PFRs in humans occurs by dermal contact following ingestion as the primary route of exposure, it is imperative to understand the fate and toxicity of OP triesters in environmental media .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The transformation of OP flame retardants in indoor and outdoor environments has been reported but has been poorly characterized . Fu et al reported the estimated half‐lives for Cl‐PFRs to be higher than those for non‐chlorinated ones using EPI Suite version 4.11 . Since the uptake of PFRs in humans occurs by dermal contact following ingestion as the primary route of exposure, it is imperative to understand the fate and toxicity of OP triesters in environmental media .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, impurities resembling compounds of interest are common in the form of intermediates from synthesis procedures, side products, and/or degradation products. Such occurrences and phenomena greatly complicate monitoring the various forms and transformations of PFRs in the environment and their subsequently becoming potential sources of human exposure . Su et al demonstrated that OP triesters with halogens and aryl functional groups are less stable than those with alkyl groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations